Medical citizenship, culture and power in perinatal and pediatric immigrant care - Challinor, Elizabeth P. (Saúde e Sociedade, 2012)
Through detailed ethnographic descriptions of Cape Verdean student migrant mothers' encounters with the Portuguese health system, based on two years of fieldwork, the aim of the paper is to elucidate the power relations inherent in institutionalised medical encounters through which cultural differences are ignored, misconstrued and criticised in order to provide a critical reflection upon the principle of equal, universal treatment for all. The observation of medical encounters constitutes part of a broader methodological approach of accompanying the mothers to appointments with doctors, social workers and immigration officials, as well as conducting semi-structured interviews with the women upon their experiences of motherhood. The ethnography not only highlights the shortcomings of a policy of blind universalism which denies difference in the name of humanism and human rights but also reveals the need to make a conceptual distinction between "health literacy" and "health systems literacy". By demonstrating how biomedical knowledge cannot be separated from the cultural context within which it is practised, the paper argues that promoting the systems literacy of immigrants who are literate in alternative health approaches and systems should be regarded as part of a wider strategy to increase the intercultural competency of doctors and patients alike. Refraining from using the term "health literacy" which implicitly labels immigrants as "illiterate", acknowledges their cultures and alternative health practices and concerns and contributes towards dissolving the knowledge hierarchies between doctors and immigrant patients.